2017
DOI: 10.4172/2471-2728.1000177
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption Potential of the Microchlorophyte Chlorella vulgaris for Some Pesticides

Abstract: Nowadays, pollution of either surface or ground water with pesticides is considered as one of the greatest challenges facing Humanity and being a national consideration in Egypt. Agricultural activities are the point source of pesticides that polluting water bodies. The present study investigated the potentiality of Chlorella vulgaris for bioremoval of pesticides mixture of 0.1 mg/mL for each component (Atrazine, Molinate, Simazine, Isoproturon, Propanil, Carbofuran, Dimethoate, Pendimethalin, Metoalcholar, Py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…For example, the immobilized algae, Chlorella sp., has been able to degrade butyltin chlorides with much higher efficacy [189]. Similar reports were furnished by Hussein et al [190], revealing that C. vulgaris was able to remove 99% of carbofuran (20 µg/L) and 98% of pendimethalin (10 µg/L).…”
Section: Algaesupporting
confidence: 72%
See 1 more Smart Citation
“…For example, the immobilized algae, Chlorella sp., has been able to degrade butyltin chlorides with much higher efficacy [189]. Similar reports were furnished by Hussein et al [190], revealing that C. vulgaris was able to remove 99% of carbofuran (20 µg/L) and 98% of pendimethalin (10 µg/L).…”
Section: Algaesupporting
confidence: 72%
“…Co(II) and Cd(II) in C. humicola can be accumulated in polyphosphate, which has a vital role in the bioremediation of heavy metals [136]. Cultivated microalgae removed various pesticides, including atrazine, molinate, simazine, isoproturn, propanil, dimethoate, carbofuran, metoalcholar, pyriproxin and pendimethalin, in the aqueous phase with the efficacy of 87-96% mainly through bioadsorption mechanisms [190].…”
Section: Biosorptionmentioning
confidence: 99%
“…The carbohydrate structure of the microalgal cell wall helps in the biosorption of toxic contaminants [9,61]. A study conducted by Hussein et al [62], reported that biosorption occurs in removing pesticides such as atrazine, carbofuran, dimethoate, and simazine by living Chlorella vulgaris. Since the ouster removal occurs within a short time, it impossible for any action for active uptake and metabolization process to take place.…”
Section: Mechanism Of Action By Microalgae Remediationmentioning
confidence: 99%
“…In the biosorption process, the solid and liquid phases containing the dissolved or suspended species to be sorbed are involved [62]. Thus, it is defined as the attachment of potentially toxic pesticides elements to the surface of microalgae.…”
Section: Biosorptionmentioning
confidence: 99%
“…Bioadsorption is a passive process (Årdal et al, 2014). Different mechanisms are involved in bioadsorption, such as electrostatic interaction, surface complexation, ion exchange, absorption, and precipitation (Bilal et al, 2018;Hussein et al, 2017). It was found that 87-96% of a number of pesticides (atrazine, simazine, molinate, isoproturn, carbofuran, propanil, dimethoate, metoacholar, pendimethalin, and pyriproxin) were removed by bioadsorption by cultivated algae.…”
Section: Optimization Of Pesticide Removal By Algal Biomassmentioning
confidence: 99%